O fechamento de uma casa de parto na perspectiva das ex-usuárias frente a uma nova gestação - Siqueira, Yeda Maria Antunes De (2017)
This was a qualitative study that aimed to understand the perception of ex-users about the closure of the Birthing center the Nursing School of the Federal University of Juiz de Fora. For the development of this study, the Grounded Theory was used as a methodological reference and the Symbolic Interactionism as a theoretical reference. Twenty ex-users of the birthing center who had a new pregnancy after the house was closed participated in the survey. In answer to the guiding question: In pregnancy after the closure of the House, how did you choose the place to have your child? The analysis of the interviews determined two categories for the study: "Birthing center" and "Experiencing a happy ending". These categories were analyzed and gave rise to three subcategories each. Thus, two diagrams emerged from the analysis. The first diagram titled "Being Held at the Birthing Center" presented the impressions women had about the care provided in the House. The second diagram, "I Am Pregnant: What Now?" Referred to women's perceptions of new gestation and expectations regarding childbirth. The Generated Theory of Data: "What Matters Is The Child Being Born Well" presented women's perceptions about the birth of their children, and their ability to adapt to their babies being born safely. The proposed theoretical model demonstrated that the closure of the Birthing center was perceived as a loss for the women, but they were able to adapt to the new situation and sought the best conditions for the birth of their babies, because for them what mattered was the child is born well.